Anti-oxidant activity of leaves and flowers extracts in chromolaena scabra plant species (L. f.) r.m. king & h. rob (2020)
Chromolaena is a genus of phanerogamic plants belonging to the Asteraceae family. They are native to America, from the southern United States to South America (especially Brazil). The species, Chromolaena scabra (L.f.) R.M. King and H. Rob, is registered in Colombia and Ecuador. Objective: The objective of this research was to determine the antioxidant activity of the leaf and flower extracts of Chromolaena scabra. Methods: The antioxidant activity was evaluated by the ABTS*+ cationic radical scavenging method (2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) and by the DPPH* radical scavenging test (radical method 1,1-diphenyl -2-picrylhydrazyl); Antioxidant activity tests were performed using Trolox's antioxidant capacity in the ABTS*+ free radical generator and its long-lasting radical scavenging capacity, which is based on the discoloration of the nitrogenous compound DPPH* . Results: The dichloromethane extract has a higher% of free radical uptake evaluated by the DPPH* method, likewise the ethanolic extract has the highest% of free radical uptake by ABTS*+ method; The evaluation of the flower and leaf extracts determined that the extract with the highest IC50 by both methods was ethanol. Conclusion: The antioxidant activity obtained by the DPPH* test was higher than that obtained by the ABTS*+ test, these values are significantly different, however, a good correlation was found between both methods, the results obtained in this study show that Chromolaena scabra has significant potential for use as a natural antioxidant agent.